Arabic Language Learning Program Management Model in Islamic Boarding Schools in Padangsidimpuan City - Zulni Hidayah Putri Lubis; Hakmi Wahyudi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study analyzes the management patterns of Arabic language learning programs in Islamic boarding schools (pesantren) in Padangsidimpuan City through three approaches: classical, four language skills, and grammar-based (qawā‘id). The study employed a qualitative field approach using interviews, observations, and document analysis. The findings show that the yellow book-based pattern defined as learning that relies on classical Islamic texts (kutub al-turāth) is the most dominant and systematically implemented, supported by structured book selection, bandongansorogan methods, and teacher guidance in text comprehension and i‘rāb analysis. The four-skills approach is applied gradually from receptive to productive skills, but its effectiveness is constrained by the lack of a supportive Arabic language environment (bi’ah lughawiyyah) and limited learning resources. The qawā‘id based pattern remains a foundational approach for understanding texts but is still largely deductive and weakly integrated with modern instructional media. Overall, these patterns complement each other, yet their implementation is hindered by limited facilities, varied student abilities, and weak program integration. This study underscores the need to improve teacher competence, learning facilities, language environments, and curriculum integration to enhance students’ communicative skills and mastery of classical texts.